The Determinants of Transfer Pricing: Tax, Intercompany Loan, Royalty, and Employee Benefits - Yunia Fausia; Nataherwin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Purpose: This study aims to analyze the effect of tax, intercompany loan, royalty, and employee benefits on transfer pricing, both partially and simultaneously. Methods: This study uses a quantitative approach with a survey method. Primary data were collected through questionnaires distributed to 100 professionals working at Public Accounting Firms in the Jabodetabek area. The respondents were selected using purposive sampling, with criteria including a work background in accounting, auditing, or taxation and an understanding of affiliated transactions and transfer pricing. The research instrument was measured using a 1–5 Likert scale. Data were analyzed using IBM SPSS Statistics through validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination. Results: The results show that tax and employee benefits have no significant effect on transfer pricing. Meanwhile, intercompany loan and royalty have a positive and significant effect on transfer pricing, with royalty being the most dominant factor. Simultaneously, all variables significantly affect transfer pricing, with an R Square value of 0.7378. Implications: These findings imply that companies should give greater attention to intercompany loan and royalty transactions when preparing transfer pricing documentation, particularly in testing transaction fairness and economic substance